Isolation and Structural Speculation of Herbicide-Active Compounds from the Metabolites of Pythium aphanidermatum - Li-hui ZHANG; Jin-lin ZHANG; Ying-chao LIU; Zhi-yan CAO; Jian-min HAN; Juan YANG; Jin-gao DONG (Journal of Integrative Agriculture, 2013)
Natural herbicides, or environment-friendly bioherbicides have been attracted more and more attentions. Isolation and structural identification of natural herbicide-active compounds from plant pathogens has been proved to be an effective approach for novel lead discovery of the pesticide development. In this study, the metabolites of the mutant strain PAM1, which obtained from PA1 of Pythium aphanidermatum (Eds.) Fitzp by ultraviolet radiation were separated and identified by HPLC, NMR, and IR. The results revealed that three active compounds including 4-hydroxy-3-methoxycinnamic acid and two indole derivatives, exhibited inhibition activity on the elongation of radical and coleoptile of Digtaria sanguinalis (L.) Scop.